Theory of technical change and economic in variance application of lie groups - Sato, Ryuzo (E. Elgar Pub., 1999)
This edition of Sato's 20-year-old work illustrates his contribution to economics. Under the heading "transformation and invariance", the book deals with a number of topics in economic theory, from production functions to the general recoverability problem of optimal dynamic behaviour.